Upaya Meningkatkan Kapasitas Hasil Biogas dengan Penambahan Stater Ragi - Arif Setyo Nugroho (Infotekmesin, 2020)
This research is expected to find out how to increase biogas production. Efforts are made by varying the ingredients for making biogas: Variations in biogas materials are 100% cow dung, and bagasse: yeast with a volume ratio of 3: 1, cow dung + bagasse with a volume ratio of 3: 1 plus 100 grams of tape yeast.  The test uses 4 kg of material in a 6 liters capacity tube. The result is the material of cow dung   coupled with bagasse and yeast tape produces the most amount of biogas when compared to other variations with the most results. The total amount of biogas originating from cow dung plus bagasse and tape yeast is at most 5.6 liters in 10 days, the least is cow dung without additional, namely 1.67 liters in 10 days. Biogas production is mostly on the 5-8 days on average, after that it has decreased in each variation.